Pemitoosan Identitas Masyarakat Boalang Mongondow Utara - Ratun Untoro (Kadera Bahasa, 2011)
Social class affects the community's behavior such as treatment and honorary system, inter or within the social class.  the research is intended to unveil the myth in North Boolaang Mongondow folktales, which constitutes the Identity of the people, using Carl Gustav Jung psychoanalysis theory.  The myth or folktale that lives in the community is the expression or the realization of unconscious wishes, which is nevertheless inconsistent, inappropriate, and do not match with daily facts.  the purpose of this research is acknowledgment the royal effort  to arrange  the community through the folktale experience. Interesting finding through the research, that the kingdom used the folktales to strengthen the royal hegemony.